Bibliometric Analysis of the Growth and Challenges of Digital Entrepreneurship - Judijanto, Loso; Mahmuddin, Mahmuddin; Fanggidae, Herny Constantia; Erwin, Erwin (Westscience Press, 2024)
This paper presents a bibliometric analysis of the growth and challenges in digital entrepreneurship, synthesizing key findings from influential research in the field. The analysis identifies major trends such as the integration of digital technologies in entrepreneurship education, the critical role of big data, and the transformation of innovation processes. It highlights how entrepreneurial ecosystems and financial innovations, such as microfinance and crowdfunding, have enabled broader access to resources for digital entrepreneurs, particularly small and medium enterprises (SMEs). Emerging themes, including social entrepreneurship, gender inclusivity, and the use of digital platforms by women entrepreneurs, reveal the shifting focus toward more inclusive and socially responsible business models. The study concludes by discussing the dynamic nature of digital entrepreneurship and the importance of developing supportive ecosystems to address the ongoing challenges of digital transformation and global competition.